Safe as houses housing inheritance in Britain - Hamnett, Chris; Harmer, Michael; Williams, Peter (Chapman, 1991)
The expansion of home ownership and rapid house price inflation since 1945 have led to dramatic changes in the role of owner occupied housing and in the composition, distribution and inheritance of wealth in Britain. This book explores these changes and some of their important economic and social consequences. Using unique data on housing inheritance the authors provide details of the occupational, income and demographic background of beneficiaries; the use to which housing wealth has been put; and the impact of housing inheritance on the housing market. They also explore the role of taxation in regulating the effects of inheritance and the extent to which the rapid growth of home ownership and house price inflation makes Britain unique amongst Western countries.
Keywords: Erfenissen; Particulier woningbezit; Sociaal-economische aspecten; Home ownership -- Great Britain; Inheritance and transfer tax -- Great Britain; Erbschaftsteuer; Wohneigentum; Großbritannien